KINDERGARTEN TEACHERS’ CHALLENGES TO THE TEACHING OF LITERACY SKILLS AMONG KINDERGARTENERS IN SHAMA DISTRICT OF GHANA - Oppong Frimpong, Samuel; Anthony, Anthony; Woode-Eshun, Woode-Eshun (Journal of Early Childhood Education (JECE), 2023)
The purpose of this study was to identify the challenges teachers face when teaching literacy skills among early graders, specifically kindergarteners and how the identified challenges impede their smooth teaching of literacy skills. The study employed ethnography design. Data was gathered through semi-structured interview guide. Purposive sampling technique was used to sample 12 participants for the interview. Data were analyzed using content and thematic analysis procedures.  The findings from the study revealed that challenges teachers encountered were related to; large class size, inadequate instructional resources, insufficient in-service training, and continuous professional development programs, learning disorders, and absence of supportive adults in the lives of kindergarteners. It was recommended that Shama District Education Directorate in collaboration with headteachers of the selected schools should organize in-service training for teachers to expose them to current trends in literacy instructional skills, train them on how to assist learners with disorders, and how to manage large class size. Again, Directorate of Education in collaboration with headteachers should organize Parent Association meetings and seminars to enlighten   parents and community members on the need to support and participate in their children’s education.